Synthesis of a highly active oxidation catalyst with improved distribution of titanium coordination states. Issue 56 (22nd June 2016) - Wu, Lizhi; Deng, Xiujuan; Zhao, Shufang; Yin, Hanmei; Zhuo, Zuoxi; Fang, Xiangqing; Liu, Yueming; He, Mingyuan
Abstract : A facile strategy was carried out to construct a high-performance titanosilicate oxidation catalyst with optimized distribution of titanium coordination states. Abstract : A facile strategy is proposed to construct a highly active oxidation catalyst with optimally distributed titanium coordination states containing "TiO4 " and "TiO6 " species. The "TiO6 " species in TS-1 + shows a superior catalytic oxidation activity, which is 2–3 times that of "TiO4 " species in TS-1.